DESIGN OF POINT OF SALES (POS) APPLICATIONS AT THE TOSCA SHOP USING THE WATERFALL METHOD - Reynold P. J. Vigeleyn Nikijuluw; Daniel Makatita (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
Kedai Tosca is a culinary business place that has quite a lot of visitors. Kedai Tosca has problems with the sales transaction system and data processing of sales transaction reports because they have not utilized the Point Of Sale (POS) system. The cashier's role is still quite simple, such as the transaction process which is still manual which is not done automatically and slows down sales transactions and transaction data processing. The POS designed and built aims to record sales transactions so as to help improve the performance of operational activities and simplify the service process. This system is capable of managing sales transaction data based on specified dates, making it easier to manage sales so as to avoid the risk of errors in financial calculations. This system can also carry out data storage processes so that report generation can run effectively and efficiently. This system was built using the programming language PHP and MySQL as its database and uses the SDLC method with the Linear Sequential Model or what is commonly called the Waterfall Model. This system can be used by Tosca Cashiers and Shop Owners in facilitating the buying and selling process and processing of Tosca Shop data properly, starting from available Menu Data, Sales Report Data, Printing menu data reports and sales reports to processing sales transactions and printing sales receipts automatically. directly quickly and computerized. For further research it is necessary to add a payment system using DANA, OVO, GoPay; calculating menu and material stock as well as Adding Features to be able to see the menu display in the transaction process